Electrodepositing of Multi-Layer Ni-Ag Coated by Copper Nanoparticles for Solar Absorber - Kadhim, Mohammed J.; Sukkar, Khalid A.; Abbas, Ahmed S. (Al-Khwarizmi Engineering Journal, 2019)
In this work, the effect of the addition of bright nickel plating and silver carried out by the electroplating method has been studied, on the coating of copper nanoparticles on the copper base metal via the process of thermal evaporation. The improvement of the solar absorber using CuNP in combination with the bright nickel and silver was obtained to be better than copper nanoparticles individually. A bright nickel enhanced the absorbed thermal stability. Also, other optical properties, absorptions, and emissivity slightly decreased from (93% to 87%), while the existence of silver had a slight impact on absorption of about (86.50%). On the other hand, thermal conductivity was evaluated using hot disk analyzer. The results showed a good improvement obtained by copper nanoparticles of about (89%) deposited on the copper substrate, while it decreased with 18.8% in the presence of bright nickel combined with copper nanoparticles. The other characteristics, like structure and phases of coating layers, were achieved using X-ray diffraction. Topographic maps were obtained using an Atomic Force Microscope and Scanning Electron Microscope.